Can Tremor Be a Rare Side Effect Related to Molnupiravir? - Sinan MERMER; İftihar KÖKSAL (Mediterranean Journal of Infection, Microbes and Antimicrobials, 2022)
While the Coronavirus disease-2019 (COVID-19) pandemic has been going on for more than two years, the drug studies required for treatment still continue. As a result of these studies, molnupiravir, which has been approved for use in many countries in the treatment of COVID-19, has been put into use in our country with the guide published on February 12, 2022. One of the most important parameters required for a drug to be used at the appropriate dose and duration is its low side-effect profile. Molnupiravir is a generally well tolerated antiviral, and the most common side effects associated with its use are diarrhea, nausea, vomiting, headache, dizziness, and rash. In this report, it was aimed to present the details of the tremor symptom that developed during molnupiravir treatment in three patients we followed up.